2009
DOI: 10.1038/hdy.2009.121
|View full text |Cite
|
Sign up to set email alerts
|

MHC genetic structure and divergence across populations of Chinook salmon (Oncorhynchus tshawytscha)

Abstract: The major histocompatibility complex (MHC) is thought to be under strong selection pressure because of its integral role in pathogen recognition. Consequently, patterns of MHC genetic variation should reflect selection pressures across the landscape. We examined genetic variation and population genetic structure at the MHC class I-A1 and class II-B1 exons in five Chinook salmon (Oncorhynchus tshawytscha) populations from two geographic regions in British Columbia, Canada. We then compared estimates of populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 84 publications
4
36
0
Order By: Relevance
“…During the larvae stage in the Quinsam population, we found evidence that offspring with lower MHC class II nucleotide divergence survived better than expected under our null hypothesis. We have previously reported that MHC class II genetic variation is dominated by a single allele in several Chinook salmon populations in British Columbia, including the Quinsam and Big Qualicum populations studied here (Evans et al 2010; also see Miller et al 1997;Neff et al 2008). This low diversity may reflect directional selection for a ''good gene'' in these populations (Neff and Pitcher 2005;Pitcher and Neff 2006).…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…During the larvae stage in the Quinsam population, we found evidence that offspring with lower MHC class II nucleotide divergence survived better than expected under our null hypothesis. We have previously reported that MHC class II genetic variation is dominated by a single allele in several Chinook salmon populations in British Columbia, including the Quinsam and Big Qualicum populations studied here (Evans et al 2010; also see Miller et al 1997;Neff et al 2008). This low diversity may reflect directional selection for a ''good gene'' in these populations (Neff and Pitcher 2005;Pitcher and Neff 2006).…”
Section: Discussionmentioning
confidence: 57%
“…These alignments were used to identify the nucleotides that encode the putative PBR-the nucleotides directly involved in the binding of pathogens-in Chinook salmon based on the known PBR in the human HLA. Sequences were also aligned to previously reported Chinook salmon MHC class I-A1 or II-B1 alleles (Evans et al 2010). …”
Section: Mhc Genotypingmentioning
confidence: 99%
See 3 more Smart Citations